Rekonstruksi Nilai Pedagogis QS. Al-Isrā’ [17]:24 dalam Pengembangan Sistem Informasi Pendidikan Anak Berbasis Nilai Qur’ani - Hidayah, Mifthahul (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This study is motivated by the lack of educational information system models for children that explicitly integrate Qur’anic normative values into their data structures, resulting in technology-based education that tends to be technocratic and detached from ethical and spiritual dimensions. This research aims to reconstruct a child education data model integrated with Qur’anic values, particularly based on the interpretation of Q.S. Al-Isrā’ [17]:24, which emphasizes compassion, parental involvement, and the continuity of education from early childhood. Employing a qualitative approach through library research, the study draws upon primary data from Qur’anic verses and non-Arabic tafsīr literature, with particular emphasis on Tafsīr al-Ibrīz. The data are analyzed using a thematic content analysis approach. The pedagogical values derived from the tafsīr analysis are then conceptually translated into a data modeling framework through a systematic mapping of normative meanings into entities and relational structures within an educational information system. The findings result in a relational schema consisting of five principal entities: child, parents, subjects, learning activities, and assessment, each embedding ethical and spiritual dimensions. This model offers an integrative framework that bridges modern information systems with an Islamic pedagogical vision centered on moral formation and compassionate relationships. Ultimately, this study contributes to the development of value-based and transformative data-driven educational systems, serving as a conceptual bridge between revelation and information technology in the context of child education.